Theoretical study of the valence and core photoemission spectra of C-60 - Colavita, Paula (My University, 2001)
The photoionization cross section and angular distribution relative to all primary ionizations in C60 have been computed employing a convergent one-centre expansion and an LDA hamiltonian over an extended energy range. The results show the presence of very sharp shape resonances both in the valence and core spectra. Good agreement is obtained with available experimental data, notably the HOMO/HOMO-1 oscillations, the absolute total photoabsorption and the available photoionization spectra, suggesting that more structure should be observable in the low energy region.
PUBLISHED
Keywords: Chemistry